Impaired dopamine release in Parkinson’s disease - Cramb, Kaitlyn M L; Beccano-Kelly, Dayne; Cragg, Stephanie J; Wade-Martins, Richard (Brain (London, England : 1878), 2023)
Abstract Parkinson’s disease is the second most common neurodegenerative disease and yet the early pathophysiological events of the condition and sequences of dysfunction remain unclear. The loss of dopaminergic neurons and reduced levels of striatal dopamine are descriptions used interchangeably as underlying the motor deficits in Parkinson’s disease. However, decades of research suggest that dopamine release deficits in Parkinson’s disease do not occur only after cell death, but that there is dysfunction or dysregulation of axonal dopamine release before cell loss. Here we review the evidence for dopamine release deficits prior to neurodegeneration in Parkinson’s disease, drawn from a large and emerging range of Parkinson’s disease models, and the mechanisms by which these release deficits occur. The evidence indicates that impaired dopamine release can result from disruption to a diverse range of Parkinson’s disease-associated genetic and molecular disturbances, and can be considered as a potential pathophysiological hallmark of Parkinson’s disease. Cramb et al. review the evidence for dopamine release deficits prior to neurodegeneration in Parkinson’s disease. They highlight the mechanisms by which these deficits occur and propose areas requiring further investigation.